2019
DOI: 10.1016/j.ijscr.2019.05.054
|View full text |Cite
|
Sign up to set email alerts
|

Sterile necrotizing and non-necrotizing granulomas in a heart transplant patient with history of PTLD: A unique finding

Abstract: Highlights This is the first ever reported case of sterile granulomas in a patient with PTLD. PTLD is a disease that could potentially be diagnosed with minimally invasive biopsy rather than diagnostic splenectomy. This report is to create awareness regarding potential presence of sterile granulomas and discuss use of biopsy before splenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…[ (e.g., lung cancer, liver cancer) varied by regions and ages, suggesting the presence of ethnicity-based and age-based differences. As the most common cause of mortality in patients with solid organ transplant, 46 we observed that the incidence of posttransplant lymphoproliferative disorders (PTLD) increased significantly in lung transplantation and the rate not influenced by age and region. Several mechanisms may explain the increased cancer risk for heart or lung transplant recipients.…”
Section: Publication Bias Analysismentioning
confidence: 89%
“…[ (e.g., lung cancer, liver cancer) varied by regions and ages, suggesting the presence of ethnicity-based and age-based differences. As the most common cause of mortality in patients with solid organ transplant, 46 we observed that the incidence of posttransplant lymphoproliferative disorders (PTLD) increased significantly in lung transplantation and the rate not influenced by age and region. Several mechanisms may explain the increased cancer risk for heart or lung transplant recipients.…”
Section: Publication Bias Analysismentioning
confidence: 89%
“…TB granulomas’ crucial constituents include neutrophils, macrophages, and lymphocytes. Necrotic granulomas house a significant number of neutrophils and eosinophils [ 37 ]. Our research indicates that a lower PNR is associated with a higher STB risk score, aligning with the previously mentioned results.…”
Section: Discussionmentioning
confidence: 99%
“…4 There are unique considerations in the transplant setting that make the approach to the differential diagnosis for granulomatous disease more challenging. Graft-versus-host disease, 12 posttransplant lymphoproliferative disease, 13 and cord colitis syndrome 14 have all been associated with tissue granulomas in transplant patients. There is also risk of drug-induced renal, pulmonary, and hepatic granulomatous inflammation from immunosuppressive therapy and prophylactic antimicrobial agents.…”
mentioning
confidence: 99%